The Systemic Administration of the Histamine H1 Receptor Antagonist/Inverse Agonist Chlorpheniramine to Pregnant Rats Impairs the Development of Nigro-Striatal Dopaminergic Neurons - Márquez-Valadez, Berenice; Aquino-Miranda, Guillermo; Quintero-Romero, Mijail-Oliver; Papacostas-Quintanilla, Helena; Bueno-Nava, Antonio; López-Rubalcava, Carolina; Díaz, Néstor Fabián; Arias-Montaño, José-Antonio; Molina-Hernández, Anayansi (Frontiers in Neuroscience, 2019)
The dopaminergic and histaminergic systems are the first to appear during the development of the nervous system. Through the activation of H1 receptors (H1Rs), histamine increases neurogenesis of the cortical deep layers, while reducing the dopaminergic phenotype (cells immunoreactive to tyrosine hydroxylase, TH+) in embryo ventral mesencephalon. Although the function of histamine in neuronal differentiation has been studied, the role of H1Rs in neurogenesis has not been addressed. For this purpose, the H1R antagonist/inverse agonist chlorpheniramine was systemically administered (5 mg/kg, i.p.) to pregnant Wistar rats (gestational days 12-14, E12-14), and control and experimental embryos (E14 and E16) and pups (21-day-old) were evaluated for changes in nigro-striatal development. Western blot and immunohistochemistry determinations showed a significant increase in the dopaminergic markers’ TH and PITX3 in embryos from chlorpheniramine-treated rats at E16. Unexpectedly, 21-day-old pups from the chlorpheniramine-treated group, showed a significant reduction in TH immunoreactivity in the substantia nigra pars compacta and dorsal striatum. Furthermore, striatal dopamine content, evoked [3H]-dopamine release and metha-amphetamine-stimulated motor activity were significantly lower compared to the control group. These results indicate that H1R blockade at E14-16 favors the differentiation of dopaminergic neurons, but hampers their migration, leading to a decrease in dopaminergic innervation of the striatum in post-natal life.